Dishonored : the veiled terror - Christopher, Adam, 1978- (Titan Books, 2018)
Billie Lurk has achieved the impossible: the Outsider has fallen. But now the Void is unbalanced, and the fate of the world is at stake. From Tyvia to Serkonos, mysterious rifts in the fabric of reality have appeared--portals into the Void, with the potential to tear the world apart. Billie's search for the source of their instability sends her far from Dunwall, to a city cut in half by a rift, and to a kingdom recovering from civil war, where an uneasy truce reigns. A former assassin, smuggler, and bounty hunter, Billie's a born survivor, and she's the only one who can set things right--but to do so she must confront her own past, with world-altering results.